Application of iterative decoding systems (UTTCM) to 4G-LTE mobile radio communication network - Elarbi Abderraouf; Mohamed Reda Lahcene; Mohammed Sofiane Bendelhoum; Abderrazak Ali Tadjeddine; Youcef Djeldjeli (Journal of Pure & Applied Sciences, 2022)
The mobile communications market has grown at an unprecedented rate and cellular phones have been adopted much faster than any other equipment. At the same time, current systems meet many needs, depending on whether mobility, speed, cost and quality are promoted and ensured ... To meet the ever-increasing demands of consumers. These large capacity demands can only be met by high efficiency and very good optimization of mobile network infrastructures, while taking into account the constraints that are power, bandwidth and limited complexity. The concern to transmit at high rates while being confined to a defined bandwidth has led some researchers to consider the application of iterative channel codes to high spectral efficiency modulations. In order to recover the transmitted data correctly and efficiently. In our paper, we are mainly interested in simulation analysis to improve the performance of 4G-LTE mobile radio transmission, through the use of iterative coding technique, which is efficient and less complex, named UTTCM through three models of channels (EPA, EVA, ETU).